Faktor-Faktor Yang Mempengaruhi Produktivitas Kerja - Joben, Joben (CV. Pusdikra Mitra Jaya, 2022)
This study aims to analyze the factors that influence work productivity. The research examines various work productivity concepts used in organizational studies, assessing them through a systematic literature review and identifying research gaps. The method employed in this research is the literature study method. The data collection technique used is literature study obtained from journals and books. Data analysis was conducted using descriptive analysis. The results of the research indicate that factors influencing employee work productivity include education, age, work environment, work experience, gender, work involvement, job satisfaction, wages, incentives, discipline, organizational culture, achievement motivation, and work creativity and leadership styles.